Facile Access to Benzothiophenes through Metal-Free Iodine-Catalyzed Intermolecular Cyclization of Thiophenols and Alkynes - Yan, Kelu; Yang, Daoshan; Zhang, Mengqi; Wei, Wei; Liu, Yao; Tian, Laijin; Wang, Hua (Synlett, 2015)
A novel iodine-catalyzed method for the synthesis of benzothiophene derivatives through cascade reactions of substituted thiophenols with alkynes has been demonstrated under metal- and solvent-free conditions. The present protocol uses inexpensive and environmentally friendly molecular iodine as the catalyst, and the corresponding products are obtained in moderate to excellent yields. Such an efficient, economical, and green transformation should provide an attractive approach to various benzothiophenes within organic and medicinal chemistry.
Keywords: iodine-catalyzed; metal-free; benzothiophenes; thiophenols; alkynes